2017
DOI: 10.1002/bdra.23621
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Exposure to Montelukast and Congenital Anomalies: A Population Based Study in Denmark

Abstract: Pregnant women with prescriptions for montelukast had a higher risk of preterm birth and maternal complications. These risks are known to be associated with maternal asthma, no increased risk of CA was found. Further analysis including more exposed pregnancies will be needed to determine the risk of specific CA. Birth Defects Research 109:452-459, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
1
23
2
3
Order By: Relevance
“…The major sequela caused by congenital ZIKV infection is microcephaly, which is evidenced in humans and animal models (Tang et al, 2016;Cui et al, 2017), and pregnant women are the direct victims of the ZIKV infection of fetus, making it vitally important that the treatment for pregnant women infection by ZIKV should be very cautious. Luckily, montelukast is classified as category B in the FDA pregnancy category and has been successfully used for treatment of pregnant women with asthma (Bakhireva et al, 2007;Cavero-Carbonell et al, 2017). Animal studies showed no adverse effects on embryo and fetal development at oral doses up to 400 mg/kg/day in rats or up to 100 mg/kg/day in rabbits, as described in the product information of montelukast (trade name Singulair R ) produced by Merck Sharp & Dohme, Ltd. With the combination of the fact that montelukast blocked vertical transmission of ZIKV in pregnant mice and its safety profile for pregnant women, it is promising that montelukast could be used for treatment of pregnant women infected with ZIKV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major sequela caused by congenital ZIKV infection is microcephaly, which is evidenced in humans and animal models (Tang et al, 2016;Cui et al, 2017), and pregnant women are the direct victims of the ZIKV infection of fetus, making it vitally important that the treatment for pregnant women infection by ZIKV should be very cautious. Luckily, montelukast is classified as category B in the FDA pregnancy category and has been successfully used for treatment of pregnant women with asthma (Bakhireva et al, 2007;Cavero-Carbonell et al, 2017). Animal studies showed no adverse effects on embryo and fetal development at oral doses up to 400 mg/kg/day in rats or up to 100 mg/kg/day in rabbits, as described in the product information of montelukast (trade name Singulair R ) produced by Merck Sharp & Dohme, Ltd. With the combination of the fact that montelukast blocked vertical transmission of ZIKV in pregnant mice and its safety profile for pregnant women, it is promising that montelukast could be used for treatment of pregnant women infected with ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…Montelukast is the leukotriene receptor antagonists successfully developed for treatment of asthmatic patients (Bakhireva et al, 2007;Cavero-Carbonell et al, 2017). However, little is known about its potential mechanism of the antiviral activity against ZIKV, DENV, and YFV.…”
Section: Montelukast Blocked Infection At the Early Stage Of Virus LImentioning
confidence: 99%
“…107,108 Registry data showed limb reduction defects with montelukast, leading to a change in the drug labeling by the FDA. 109 Zileuton is best avoided in pregnancy due to inadequate data. 110 Safety data for biologics are limited to registry data, with no human studies available.…”
Section: Vasoconstrictive Effect Is Concerning In Pregnancymentioning
confidence: 99%
“…Montelukast was associated with a similar safety profile to placebo and was well tolerated with minimal adverse effects. Montelukast is classified as pregnancy risk category B1; studies in asthma have indicated an increased risk in of preterm birth and maternal complications, but no increased risk of congenital anomalies …”
Section: Resultsmentioning
confidence: 99%
“…Montelukast is classified as pregnancy risk category B1; studies in asthma have indicated an increased risk in of preterm birth and maternal complications, but no increased risk of congenital anomalies. 51…”
Section: Leflunomidementioning
confidence: 99%